2017
DOI: 10.1097/ncc.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Supportive Care Needs of Men With Locally Advanced and Metastatic Prostate Cancer on Hormonal Treatment

Abstract: Despite national cancer reforms, unmet supportive care needs persist. The findings from this study may be central in the re-design of future services to optimize men's quality of life and satisfaction with care. Clinicians are encouraged to use these finding to help them optimize care delivery and individual quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
81
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(92 citation statements)
references
References 43 publications
7
81
0
4
Order By: Relevance
“…Androgen deprivation therapy (ADT) for metastatic prostate cancer remains the mainstay of treatment and has been proven to be effective in controlling disease (Sternberg et al, 2013). The majority of men face a range of physical and psychological problems that can have a profound decrement on quality of life and exacerbate the need for supportive care (Cockle-Hearne et al, 2013;King et al, 2015;Paterson et al, 2017;Watson et al, 2016). The treatment specific side effects include hot flushes, osteoporosis, fatigue, sexual dysfunction, changes in muscle mass, adiposity, and psychological effects such as, mood disturbance, cognitive impairment, difficulties with self-image and masculinities (Fitzpatrick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Androgen deprivation therapy (ADT) for metastatic prostate cancer remains the mainstay of treatment and has been proven to be effective in controlling disease (Sternberg et al, 2013). The majority of men face a range of physical and psychological problems that can have a profound decrement on quality of life and exacerbate the need for supportive care (Cockle-Hearne et al, 2013;King et al, 2015;Paterson et al, 2017;Watson et al, 2016). The treatment specific side effects include hot flushes, osteoporosis, fatigue, sexual dysfunction, changes in muscle mass, adiposity, and psychological effects such as, mood disturbance, cognitive impairment, difficulties with self-image and masculinities (Fitzpatrick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Men affected by metastatic prostate cancer are likely to have a long illness pathway, as well as the individual burden to patients and their partner/caregivers with the associated side-effects, and this represents a burden on healthcare resources internationally (Carter et al, 2011;Chambers et al, 2018;Paterson et al, 2015a;Paterson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in our study only 30% of NET patients reported that their informational needs were mostly or fully met at diagnosis. Other studies have also reported that for patients with more prevalent cancers, satisfaction and accessibility relating to hospitals and both diagnostic and therapeutic tools is superior and travel time shorter than for those with rarer cancers …”
Section: Discussionmentioning
confidence: 99%
“…88%) . A U.K. study of men with prostate cancer reported only 3.2% felt they had a strong need for more information on their care, diagnosis or treatment, while 48.4% felt this need was met fully . Similarly, a Japanese study of breast cancer survivors demonstrated that 78.8% were satisfied with information they received on the disease and therapy at diagnosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation